The Level of Innovation Towards SME Manufacturing Industries in Johor - Zamri, Nur Mirza Afiqah; Azizan, Anim Zalina (Research in Management of Technology and Business, 2020)
The presence of this Small and Medium Enterprise (SMEs) has given and opened a wide scope of job opportunities especially to low-pay rustic populaces. This is because there are numerous business opportunities in different sectors that can be explored in SMEs. However, the requirements and weaknesses looked by most SME entrepreneurs are the failure of the companies to innovate in developing product markets and fordable in methodical techniques. The purpose for this study is to recognize the level of product innovation, process innovation, position innovation and paradigm innovation also the factors that influencing the innovations in SMEs Johor. This study utilizes quantitative techniques where the questionnaires will be circulated to SMEs managers in Johor. This study will be directed utilize a simple sampling method. The information will analyze using descriptive test. From the result it showed that overall SME in Johor has adequate high level on competencies in innovation. Therefore, it can be concluded that SME in Johor are innovative enough to remain in competitive advantages.